Fullerenes with Structure of Cubic and Octahedral Type - Sánchez-Bernabe, F.J. (Веснік Брэсцкага ўніверсітэта. Серыя 4. Фізіка. Матэматыка, 2020)
Several fullerenes that resemble Cubic or Octahedral structure are presented, between them a molecule with 128 carbons, and another one with 132.